2020
DOI: 10.1177/2396941519900076
|View full text |Cite
|
Sign up to set email alerts
|

Problem behavior in young children referred with language difficulties: Relations to language and intentional communication

Abstract: Background and aims: This exploratory study aims to examine the relative contribution of language and intentional communication to internalizing and externalizing problem behavior. Methods: Twenty-nine Dutch-speaking children (age range 24-46 months) referred with language difficulties participated in this study. For the majority of children, these early language difficulties appeared to be part of a broader neurodevelopmental disorder, mainly autism spectrum disorder. Parent ratings on the Achenbach Child Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…Children with communication challenges need practical strategies to provide support for social communication to increase quality classroom interactions. Walton (2018) asserts that Department of Education policies have placed priority on the field of inclusive education, which calls for educators to be informed about its principles and practices and be capable of instructing various student populations (Walton, 2018) If problem behavior may compromise the development of young children with language difficulties, it is important to understand the factors associated with its onset and persistence so that intervention can be successful (Jansen, Maljaars, Verhappen, Zink, Steyaert & Noens, 2020). This study focuses on the importance of communication in controlling behaviour of deaf learners.…”
Section: Challenges Faced By Learners With Hearing Lossmentioning
confidence: 99%
“…Children with communication challenges need practical strategies to provide support for social communication to increase quality classroom interactions. Walton (2018) asserts that Department of Education policies have placed priority on the field of inclusive education, which calls for educators to be informed about its principles and practices and be capable of instructing various student populations (Walton, 2018) If problem behavior may compromise the development of young children with language difficulties, it is important to understand the factors associated with its onset and persistence so that intervention can be successful (Jansen, Maljaars, Verhappen, Zink, Steyaert & Noens, 2020). This study focuses on the importance of communication in controlling behaviour of deaf learners.…”
Section: Challenges Faced By Learners With Hearing Lossmentioning
confidence: 99%
“…For example, children with internalizing behavior problems are more likely to be anxious and withdrawn from social situations with peers and adults, less likely to initiate interactions or to participate actively in the classroom; whereas children with externalizing behaviors are more likely to exhibit aggressive behaviors toward others (Baker et al, 2008; Hymel et al, 1990; Ladd & Troop-Gordon, 2003). Both internalizing and externalizing behaviors negatively impact a child’s ability to succeed, and they are also associated with different types of language deficits (Chow & Hollo, 2018; Jansen et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Also, it is widely known that a certain struggle in language development, as vocabulary, expression, and reading, can be associated with problems in behavior (Peterson et al, 2013;Jansen et al, 2020). It has been reported that young children with language difficulties might develop problem behavior (Henrichs et al, 2013) which can get worse over time (Curtis et al, 2018).…”
Section: Hurdles For Second Language Learnersmentioning
confidence: 99%